Lower limb balance, ankle dorsiflexion, orofacial tissue pressure, and occlusal force of rugby players - Rafael R. Machado; Marcelo Palinkas; Paulo B. de Vasconcelos; Sara Gollino; Veridiana W. Arnoni; Marcos Vinicios R. Prandi; Isabela H. Regalo; Selma Siéssere; Simone C.H. Regalo (Sports Medicine and Health Science, 2024)
This cross-sectional study examined the lower limb balance, ankle dorsiflexion, orofacial tissue pressure, and occlusal strength of rugby players. Twenty-six participants were divided into groups: rugby players (n ​= ​13) and healthy sedentary adults (n ​= ​13). Participants underwent an analysis of lower limb balance using a composite score (Y-Balance Test). Ankle dorsiflexion was measured using the Lunge Test. The Iowa Oral Performance Instrument was employed to measure orofacial tissue pressure. Bite force was measured with a dynamometer, and T-Scan assessed occlusal contact distribution. Data were analyzed using the t-test (p ​< ​0.05) and ANCOVA with age and weight as covariates, where it is possible to verify that these factors did not influence the results obtained. Significant differences were observed in the balance of the right (p ​= ​0.07) and left (p ​= ​0.02) lower limbs, where rugby players had lower composite scores. There were significant differences in the right (p ​= ​0.005) and left (p ​= ​0.004) lunges, with rugby players showing lower values, as well as lower tongue pressure (p ​= ​0.01) and higher lip pressure (p ​= ​0.03), with significant differences to sedentary participants. There was no significant difference in molar bite force and distribution occlusal contacts between groups. Rugby seems to reduce lower limb displacement, cause ankle hypomobility, lead to changes in orofacial tissues, particularly the tongue and lips. This study is significant for identifying significant differences between rugby players and sedentary individuals, providing new insights into the impact of rugby on health and performance, which can benefit sports training and injury prevention.